Clima organizacional y su impacto en el rendimiento productivo en el recurso humano en la empresa “La Huerta” S.A.S, 2023 - Alvarez Alvarez, Maritza Luxila (2024)
The objective was to identify the relationship that exists between the Organizational Climate and the sustainable productive development of the company “La Huerta” S.A.S. The results show a magnificent interdependence of human resources, maintaining open communication, mutual respect, effective teamwork and a healthy work environment that contribute significantly to increasing the motivation, commitment and satisfaction of employees. It was necessary to use types of research such as: field research that allowed us to see the current situation in which the company was, descriptive, documentary, correlational and explanatory research, methods were also used to construct the methodology of the research object. We found a small population and sample since the company is very small and has few employees. For that reason, observation and census techniques were used, which was carried out using Google forms using the Likert scale. This type of environment promotes a sense of belonging and collaboration, resulting in greater productivity and efficiency in each of the operations carried out by the company. The corporate culture, leadership, Human Resource policies, internal communication, and interpersonal relationships were established, with the impact on the ethics, morals, motivation and productivity of employees. Areas of strength and improvement that need to be encouraged and that require the necessary attention were also identified. The productivity of human resources has proven to be a determining factor in profitability, competitiveness and growth of the company, the strengths highlight the efficiency of the commitment of the work team, the ability to adapt to the changing challenges of the business environment.